HAPPINESS IN FOCUS – MEASURING METAPHYSICAL CONCEPT FOR COUNTRY STRATEGY AND ORGANIZATIONAL RECOMMENDATIONS - Carvalho, Marcos Bacellar de; Gonçalves, Carlos Alberto; Pardini, Daniel Jardim (Revista de Administração da UFSM, 2010)
For Aristotle, Happiness should be ultimate reason for life. Researchers have demonstrated that Happiness is positively correlated with creativity and productivity. So, the subject is relevant for each one as well as for organizations. Bentham’s Utility Principle proposed that each people action should be judged according its final contribution to Happiness, whether positive or negative. Now the question of this work arises: are the organizational concepts (e.g.: Innovation, Competitiveness, Sustainability, Quality of Life), so frequent in administration technical literature, "useful" for Happiness? Are they "useful" for people as well as for organizations? The analysis of an interrelationship model proposed, covering such concepts, has positively answered this question. Hume (1741) and Bentham’s proposal, in which administrators should take Happiness in account when establishing their government strategy, is very actual.